2022
DOI: 10.3390/foods11233881
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Pesticide Residue Levels on the Hami Melon Surface Using Multiscale Convolution

Abstract: Pesticide residues directly or indirectly threaten the health of humans and animals. We need a rapid and nondestructive method for the safety evaluation of fruits. In this study, the feasibility of visible/near-infrared (Vis/NIR) spectroscopy technology was explored for the discrimination of pesticide residue levels on the Hami melon surface. The one-dimensional convolutional neural network (1D-CNN) model was proposed for spectral data discrimination. We compared the effect of different convolutional architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The reference measurement was performed after spectral data acquisi ence values of the pesticide residue contents were measured in the Food Q sion and Testing Center (Shihezi), Ministry of Agriculture and Rural Affa urement procedure was consistent with Yu et al [15]. (1) Standard preparat ard mixture intermediate and working solutions were prepared in n-hexa tration of 20.0 mg/mL and 1.0 mg/mL, respectively.…”
Section: Reference Measurement Of the Pesticide Residue Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference measurement was performed after spectral data acquisi ence values of the pesticide residue contents were measured in the Food Q sion and Testing Center (Shihezi), Ministry of Agriculture and Rural Affa urement procedure was consistent with Yu et al [15]. (1) Standard preparat ard mixture intermediate and working solutions were prepared in n-hexa tration of 20.0 mg/mL and 1.0 mg/mL, respectively.…”
Section: Reference Measurement Of the Pesticide Residue Contentsmentioning
confidence: 99%
“…A single-scale, one-dimensional convolutional neural network (1D-CNN) was proposed to recognize pesticide residues (lambda-cyhalothrin, trichlorfon, phoxim, and mixtures of trichlorfon and phoxim) on garlic chive leaves, achieving a better accuracy of 97.9% [13]. 1D-CNN models using multiscale convolution were proposed to identify the types and levels of pesticide residues on the Hami melon [14,15]. The test results showed that the multiscale convolution networks provided a better model performance than the single-scale networks.…”
Section: Introductionmentioning
confidence: 99%